Industry Competitiveness Impacts of National ETS in China and Policy Options. (August 2015) - Lin, Wenbin; Liu, Bin; Gu, Alun; Wang, Xin
Abstract: China is busy constructing its domestic national ETS after one year's operation of six pilot ETS. The competitiveness impacts of national ETS on industries, especially in terms of price increment, production loss in both domestic and oversea markets, are severely discussed among not only industry but also academic. This paper intends to quantify these two dimensions of competitiveness using an economic model combined with input-output methods. Based on the model results, we discuss about the CO2 price setting, pass through rate of electricityprice and allowance allocation method in the forthcoming national ETS and make policy implications for Chinese policy marketers, in order to make balance between CO2 emission reduction and industry developing.